Vrtec in družinsko okolje kot napovednika govorne kompetentnosti šestletnih otrok - Marjanovič Umek, Ljubica (Sodobna pedagogika, 2008)
This study examines different factors of children's language competence at 6 years of age, namely the duration of child's enrolment into preschool, parental education, characteristics of home environment and child's intellectual abilities. The sample included 147 Slovenian children, approximately 6 years old, who were attending first grade at the time of the assessment. Prior to primary school children attended preschool for 5, 3, or 0 years. The findings suggest that parental education and home environment along with child's gender and intellectual abilities represent important predictors of child's language competence as they explain a sustantial share of variance in children' language comprehension, expression, meta-linguistic awareness and storytelling ability. The duration of child's enrolment into preschool explains only a small share of additional variance in language comprehension, expression and storytelling ability and an important share of variance in children's meta-linguistic awareness. The duration of child's enrolment into preschool is an important predictor of his/her storytelling ability. Children who, prior to entering primary school, attended preschool for three years, told stories on the highest developmental levels. The finidngs were interpreted in the light of the role of child's home environment and the opportunities offered by different preschool activities for supporting toddler's/child's language development.
Keywords: družinsko okolje; govorni razvoj; jezikovni razvoj; otroška psihologija; otroški vrtci; predšolska vzgoja; predšolski otroci